Customer satisfaction of the foreign exchange department Prime Bank Limited, Mouchak Branch - Tabassum, Anika (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.